(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
The notion of rock-bottom is widely used in the treatment of addiction and can be described in existential terms as an event of truth. Addiction is described as an attempt to technocratically alter the lived-texture of being while recovery is being open, while acknowledging the finitude that is humanity’s essential nature